Hepatitis B Infection Among Pregnant Women in China: A Systematic Review and Meta-Analysis - Liu, Dan; Liu, Yan; Ni, Jiaqi; Li, Hailong; Zeng, Linan; Zhang, Chuan; Zhang, Li; Yu, Qin; Wu, Bin; Zhang, Lingli (Frontiers in Public Health, 2022)
Background A study of the current situation and characteristics of hepatitis B virus (HBV) infection among Chinese pregnant women is meaningful to provide baseline information for future research and policy making, with an aim to eliminate HBV in China. Objectives To provide the epidemiological status of HBV infection among pregnant women in China. Methods PubMed, EMbase, The Cochrane Library, and three Chinese databases were searched. Cohort studies and cross-sectional studies on HBV prevalence in Chinese pregnant women, published after 2016, were retrieved. In addition, combined HBV prevalence and 95% confidence interval (CI) were calculated. This research was registered in PROSPERO (CRD42021289123). Main Results A total of 42 studies were included in the study, with a sample size of 4,007,518 cases, and 20 provinces in China. The prevalence of HBV in Chinese pregnant women was 6.64% (95% CI: 5.72–7.57%) during the period between 2016 and 2021. Among HBsAg positive pregnant women, the HBeAg positive rate was 25.80% (95% CI: 22.26–29.69%). Moreover, geographic regions with HBV prevalence ranking from high to low were in western China, eastern China, and central China, successively. Conclusion The prevalence of HBV in Chinese pregnant women is intermediate endemic, although disparities exist between different regions. Among pregnant women with HBV infection, a high proportion of the patients have strong infectivity. Factors affecting HBV prevalence remain controversial, which demands further studies. Systematic Review Registration https://www.crd.york.ac.uk/PROSPERO/, identifier: CRD42021289123.